The Application of Quadratic Bezier Curve on Rotational and Symmetrical Lampshade - Octafiatiningsih, Erny; Sujarwo, Imam (CAUCHY, 2016)
The procedure of constructing lampshade is through parameter merger and selection of Bezier surfaces shapeshifters; thus it producesperfect and varied sitting-lampshades.Constructing sitting-lamp shades requires the study of the physical (lighting) and geometryaspects. In terms of geometry, the existed sitting-lampshade creation models is generally monotonous and constructed from objects pieces. In line with these problems, this research is divided into four stages:First, preparing the data to build a sitting-lampshade. Second, technical studying to construct the symmetricity of the sitting-lamp shade shape.Third, constructing the parts of the sitting-lampshade, namely the base, the main part, the roof. Fourth, constructingthe complete sitting-lampshade. The results of this research to obtain the procedures of constructing the sitting-lampshade namely: First, dividing the major axis into three non-homogeneous sub segments.Second, constructing parts of the sitting-lampshade namely the base, the main part, and the roof by combining the sitting-lamp shade components from the geometrical objects deformation.Third, filling each sub segment of non-homogeneous parts with parts of the lampshade and creating the boundary curvesproducing a varied innovative symmetricalmodels of sitting-lampshade.